Enablers of psychological well‐being for refugees and asylum seekers living in transitional countries: A systematic review. (11th November 2018) - Posselt, Miriam; Eaton, Heather; Ferguson, Monika; Keegan, David; Procter, Nicholas
Abstract: The purpose of this systematic review was to locate and synthesise existing peer‐reviewed quantitative and qualitative evidence regarding enablers of psychological well‐being among refugees and asylum seekers living in transitional countries and for whom migration status is not final. Systematic searches were conducted in nine databases: Academic Search Premier, CINAHL, Embase, Emcare, Medline, Psychology and Behavioral Science, PsycINFO, Scopus, and Web of Science. Search terms were related to refugees and asylum seekers, enablers, and psychological well‐being. Studies were limited to those conducted in the last 20 years, with participants who were refugees and asylum seekers with no legal residency status, aged 16 years and above, and living in transit host countries without UNHCR resettlement programmes. This systematic review was conducted between March and June 2018 and followed the PRISMA guidelines. Results were screened by two reviewers at two stages: title and abstracts, and full‐text. Critical appraisal and data extraction were also completed by two reviewers. Initial database searching yielded 3, 133 results. Following the addition of two records from relevant reference lists and the removal of duplicates, a total of 1, 624 results were included for screening. A total of 16 articles were deemed eligible for inclusion in this review, reporting on a collective sample of 1, 352 participants. Twelve qualitative and four quantitative studies identified eight enablers of psychological well‐being: social support; faith, religion and spirituality; cognitive strategies; education and training opportunities; employment and economic activities; behavioural strategies; political advocacy; and environmental conditions. Despite many challenges associated with forced displacement and the transit period, this review highlights multiple factors that promote well‐being and suggest areas for intervention development and resource allocation.